Zebrafish MARCH8 downregulates fish IFN response by targeting MITA and TBK1 for protein degradation. (October 2022) - Zhao, Xiang; Dan, Cheng; Gong, Xiu-Ying; Li, Yi-Lin; Qu, Zi-Ling; Sun, Hao-Yu; An, Li-Li; Guo, Wen-Hao; Gui, Jian-Fang; Zhang, Yi-Bing
Abstract: Recent studies have related the membrane-associated RING–CH–type finger (MARCH) family proteins to host innate immune response. Zebrafish ( Danio rerio ) MARCH8 is reported to target SVCV glycoprotein for degradation; however, little is known about whether fish MARCH8 is involved in innate interferon (IFN) response. In this study, zebrafish march8 was significantly induced by SVCV infection. Overexpression of MARCH8 diminished fish IFN-mediated antiviral response, thus promoting the replication of SVCV and GCRV in fish cells. Mechanistically, MARCH8 interacts with and degrades MITA and TBK1 proteins to inhibit IFN response. Moreover, MARCH8 has an E3 ligase activity and enhances MITA and TBK1 polyubiquitination. Our findings reveal a mechanism whereby zebrafish MARCH8 downregulates fish IFN response and facilitates viral replication by targeting MITA and TBK1 for protein degradation. Highlights: Zebrafish march8 was a virus-inducible gene. Overexpression of zebrafish MARCH8 promoted viral infection by downregulating fish IFN response. MARCH8 decreased fish IFN response by interacting and facilitating protein degradation of MITA and TBK1. MARCH8 promoted the polyubiquitination of MITA and TBK1.